Системи "on-line підтримки" як складова стратегії реформування вищої освіти - Ігуменцева, Наталія Володимирівна; Овсюченко, Юрій Вікторович; Пересада, Олена Василівна; Прібильнова, Інна Борисівна (НТУ "ХПІ", 2019)
Робота присвячена дослідженню впливу застосування автоматизованих ботів-консультантів у прийнятті управлінських рішень щодо підвищення ефективності менеджменту у закладах вищої освіти в умовах реформування. Проаналізовано сучасні умови щодо реформування вищої освіти в Україні та визначено напрямки інтеграції у світовий освітній процес. Реформування вищої освіти передбачає забезпечення конституційних прав громадян на якісну освіту та рівний доступ до якісної освіти, регіональна система управління відомствами щодо забезпечення національних, регіональних та місцевих інтересів, а також інтересів усіх суб'єктів національної системи відомства України. Встановлено, що набуває розвитку застосування автоматизованих систем управління у закладах освіти за кордоном. Одним з різновидів цього є CRM-система. Рекомендовано застосовувати наведений підхід у закладах вищої освіти в Україні. Запропоновано використовувати роботу CRM-системи у закладах вищої освіти України, що передбачає запровадження автоматизованих систем «оn-line підтримки» прийняття управлінських рішень адміністрацією на основі залучення й обробки інформації, що охоплює питання фінансово-економічного, правового та соціального напрямів діяльності навчального закладу й сприяє підвищенню його конкурентоспроможності в умовах інтеграційного реформування. Визначено сутність поняття головного стейкхолдера закладу вищої освіти. Рекомендовано впровадження гнучкої автоматизованої системи матеріального стимулювання в закладах вищої освіти. Визначено, що застосування інноваційних технологій у роботі CRM-системи має забезпечити прозорість, підвищити рівень задоволеності співробітників і попередити абсентеїзм.

The work is devoted to the study of the impact of the use of automated bots of consultants in making managerial decisions on improving the efficiency of management in higher education institutions in the conditions of reform. The current conditions for the reform of higher education in Ukraine are analyzed and directions of integration in the world educational process are determined. Higher education reform is to consume the constitutional rights of citizens to high-quality higher education and equal access to high-quality higher education, reorganization of the system of higher education management in order to protect the national, regional and local interests, as well as the interests of all subjects of the national system of higher education of Ukraine. It is established that the development of application of automated control systems in educational institutions abroad is becoming. One of the varieties of this is the CRM-system. It is recommended to apply the above-mentioned approach in higher education institutions in Ukraine. It is proposed to use the work of the CRM-system in higher education institutions of Ukraine, which involves the introduction of automated systems of "on-line support" for the adoption of administrative decisions by the administration on the basis of the attraction and processing of information that covers the issues of financial and economic, legal and social activities of the educational institution and promotes increase its competitiveness in conditions of integration reform. The essence of the notion of the main stakeholder of a higher educational institution is defined. The introduction of a flexible automated system of material incentives in higher education institutions is recommended. It is determined that the use of innovative technologies in the work of the CRM system should ensure transparency, increase the level of employee satisfaction and prevent absenteeism.
"On-line support" systems as a component of strategy of reformation of higher education
Keywords: CRM-система; головний стейкхолдер; абсентеїзм; стратегія реформування освіти; інноваційні технології; CRM system; main stakeholder; absenteeism; education reform strategy; innovative technologies